Patient-Reported Outcomes in Pediatric Cancer Registration Trials: A US Food and Drug Administration Perspective. (30th April 2021) - Murugappan, Meena N; King-Kallimanis, Bellinda L; Reaman, Gregory H; Bhatnagar, Vishal; Horodniceanu, Erica G; Bouchkouj, Najat; Kluetz, Paul G
Abstract:  : Pediatric patient-reported outcome (PRO) data can help inform the US Food and Drug Administration's (FDA's) benefit-risk assessment of cancer therapeutics by quantifying symptom and functional outcomes from the patient's perspective.  : This study assessed use of PROs in commercial pediatric oncology trials submitted to the FDA for regulatory review. FDA databases were searched to identify pediatric oncology product applications approved between 1997 and 2020. Sponsor-submitted documents were reviewed to determine whether PRO data were collected, which instruments were used, and the quality of collected data (ie, sample size, completion rates, and use of fit-for-purpose instruments). The role of PROs in each trial (endpoint hierarchy) was also recorded in addition to whether any PRO endpoints were included in product labeling.  : We reviewed 17 pediatric oncology applications, 4 of which included PRO data: denosumab, tisagenlecleucel, larotrectinib, and selumetinib. In these 4 instances, PROs served as exploratory endpoints and were not incorporated in product labeling. Trials that collected PRO data were phase II or phase I/II single-arm studies with sample sizes of 28 to 88 patients. Symptomatic adverse events (AEs) were characterized using clinician-reported Common Terminology Criteria for Adverse Events (CTCAE) without additional patient self-report.  : PROs were infrequently used in pediatric cancer registration trials. When PROs were used, PRO data were limited by lack of a clear research objective and corresponding prospective statistical analysis plan. Contemporary PRO symptom libraries, such as the National Cancer Institute's Pediatric PRO-CTCAE, may provide an opportunity to better evaluate the occurrence and impact of symptomatic AEs, from the patient's perspective, in pediatric oncology trials.